Determinants of the choice of multi-governance structures by producers and processors of paddy in Benin - Codjo, Simon Ogoudélé; Kpenavoun Chogou, Sylvain; FIAMOHE, ROSE EDWIGE; ACCLASSATO, HOUENSOU DÉNIS; BIAOU, GAUTHIER (My University, 2019)
This study aims to analyse the factors that influence the selection of governance structures by rice producers and processors in Benin. Unlike previous studies, the factors that influence the selection of governance structures are identified simultaneously for both producers and processors of paddy. Data were collected in Benin from about 300 producers and 140 processors of paddy randomly selected. The results indicate that 78% of producers and 92% of the processors use spot market for paddy transaction. Around a quarter of producers use at least two governance structures to sell paddy. Producers and processors belonging to an innovation platform are more likely to use formal contracts in their transactions. Also, producers and processors are more likely to use credit payment mechanism with formal contract. The findings suggest that innovation platforms can be used to facilitate contractual relationships between paddy producers and processors.
Keywords: Multivariate probit; market dynamics; African rice value chains; governance mechanisms.